Optimization of air termination system by digital modelling method - Struzewski, P. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2009)
The paper deals with the principles of design of the digital model intended for the assessment of the effectiveness of three lightning rods protecting two buildings in Polish Olshtyn-South substation 110/15 kV. The purpose of the model application is a selection of the optimal placement of these rods that would assure maximum buildings safety. As a result, recommendations of lightning rods placement that guarantees minimal lightnings frequency to the substation buildings were developed. Розглянуто принципи побудови цифрової моделі для оцінки ефективності грозозахисту за допомогою тристрижневих громовідводів, які забезпечують безпеку двох будівель польської підстанції 110/15 кВ "Ольштин-Південь". Результатом моделювання є отримані рекомендації щодо розташування громовідводів, що гарантує мінімальну частоту ударів блискавки в будівлі підстанції.